2013
DOI: 10.1111/ddg.12193
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in untreated patients with psoriasis: case‐control study

Abstract: reported in psoriatic patients. Total sperm count, sperm mo-tility and percent of spermatozoa with normal morphology were significantly reduced in patients compared to controls. suPAR levels were significantly increased in patients compared to controls and found to be above the reference limits. Ultrasound signs of inflammation of the accessory glands were observed in 35/50 patients with psoriasis and in none of the controls. Conclusion: Our study suggests that untreated psoriasis may impair male fertility. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 34 publications
2
28
2
5
Order By: Relevance
“…Damevska et al. obtained similar figures in their case‐control study . Albeit statistically not significant, our study revealed a higher body weight, BMI, and obesity rate in patients with pathological myocardial scintigraphy.…”
Section: Discussionsupporting
confidence: 85%
“…Damevska et al. obtained similar figures in their case‐control study . Albeit statistically not significant, our study revealed a higher body weight, BMI, and obesity rate in patients with pathological myocardial scintigraphy.…”
Section: Discussionsupporting
confidence: 85%
“…Triglyceridemia was significantly more prevalent in Group B [143/236(60.59%) patients], than in Group A (51.27%). Similarly, hypertriglyceridemia and abdominal obesity were strongly associated with psoriasis in the Damevska et al () study. Although the HDL cholesterol levels were found to be reduced in our patients.…”
Section: Discussionmentioning
confidence: 70%
“…A Danish research investigating the Danish National Patient Register for the period 1977–2001 identified a total of 1,074 (0.36%) of the schoolchildren with psoriasis. Multivariate analysis demonstrated an association between excess increase in body mass index and psoriasis in females only (Damevska, Neloska, Gocev, & Mihova, ). Wherein, the females showed a significant association between psoriasis and body mass index at ages 12 ( p = .028) and 13 years ( p = .010).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the burden of psoriatic arthritis, some studies suggest that people with psoriasis, particularly those with severe disease, may be at increased risk of cardiovascular disorders. Associations with other co‐morbidities such as metabolic syndrome, chronic obstructive pulmonary disease, liver disease, renal failure, lymphoma and non‐melanoma skin cancer, and rheumatoid arthritis, have also emerged (Damevska, Neloska, Gocev, & Mihova, ; Gottlieb, Chao, & Dann, ).…”
Section: Understanding Reasons For Cam Use Among Patients With Psoriasismentioning
confidence: 99%